Enhanced Recovery Components for Posterior Lumbar Spine Fusion: Harnessing National Data to Compare Protocols. Issue 1 (February 2022) - Echt, Murray; Poeran, Jashvant; Zubizarreta, Nicole; Girdler, Steven J.; Mazumdar, Madhu; Galatz, Leesa M.; Memtsoudis, Stavros G.; Hecht, Andrew C.; Chaudhary, Saad
Abstract : Study Design: This was a retrospective cohort study. Objective: The aim of this study was to assess the most commonly used components of enhanced recovery after surgery (ERAS) combinations and their relative effectiveness. Summary of Background Data: Data is lacking on use and effectiveness of various ERAS combinations which are increasingly used in spine surgery. Materials and Methods: Posterior lumbar fusion cases were extracted from the Premier Healthcare claims database (2006−2016). Seven commonly included components in spine ERAS protocols were identified: (1) multimodal analgesia, (2) tranexamic acid, (3) antiemetics on the day of surgery, (4) early physical therapy, (5) no urinary catheter, (6) no patient-controlled analgesia, and (7) no wound drains. Outcomes were: length of stay, "any complication, " blood transfusion, and hospitalization cost. Mixed-effects models measured associations between the most common ERAS combinations and outcomes, separately for 2006−2012 and 2013−2016. Odds ratios (ORs) and 95% confidence intervals (CIs) are reported. Results: Among 97, 419 (74%; 2006−2012) and 34, 932 (26%; 2013−2016) cases ERAS component variations decreased over time. The most commonly used combinations included multimodal analgesia, antiemetics, early physical therapy, avoidance of a urinary catheter, patient-controlled analgesia and drains (10% n=9401 and 19% n=6635 in 2006−2012 and 2013−2016, respectively), and did not include tranexamic acid. Multivariable models revealed minor differences between ERAS combinations in terms of length of stay and costs. The most pronounced beneficial effects in 2006−2012 were seen for the second most commonly (compared with less often) used ERAS combination(s) in terms of blood transfusion (OR: 0.65; CI: 0.59−0.71) and "any complication" (OR: 0.73; CI: 0.66−0.80), both P <0.05. In 2013−2016 the third most commonly used ERAS combination showed the strongest effect: blood transfusion OR: 0.63; CI: 0.50−0.78, P <0.05. Conclusions: ERAS component variations decreased over time; maximum benefits were particularly seen in terms of transfusion and complication risk reduction. These findings may inform future ERAS utilization and clinical trials comparing various ERAS protocols.